Pernikahan Di Bawah Umur Dalam Perundang- Undangan Di Indonesia Perspektif Hukum Islam - Sri Hariati; Musakir Salat (Universitas Mataram, 2023)
Marriage is a very important momentum for the journey of human life. Besides bringing the bride and groom to a different realm, marriage will also automatically change the status of both. After marriage, both parties will receive a heavy burden and responsibility according to their respective natures. Responsibilities and burdens are not something that is easy to carry out, so they must be able to bear and carry them out. The purpose of this research is to find out how underage marriage is in the legislation in Indonesia from the perspective of Islamic law. The research method used is Normative legal research, namely the method or method used in legal research that places law as a building system of norms. The results obtained are factors that cause underage marriages, namely customary and cultural factors, economic factors, religious factors, educational factors, matchmaking factors by both parents, and child willingness factors. Underage marriages in terms of Islamic law are only required to have reached puberty between the two prospective husbands and wives. As for the impacts caused by underage marriages, namely positive and negative impacts on both parties of the bride and groom such as in household life both health, education and the economy. In addition, there are efforts to prevent underage marriages.